Use of cytoplasmic male sterility in sorghum breeding for productivity - N. A. Kovtunova; A. E. Romanyukin; V. V. Kovtunov; G. M. Ermolina; E. A. Shishova (Зерновое хозяйство России)
The productivity increase of many agricultural crops is associated with the production of heterotic hybrid forms that are more productive than conventional varieties. In order to obtain a heterotic effect and develop hybrid seeds in sorghum breeding practice, the phenomenon of cytoplasmic male sterility is used. The purpose of the current work was to study new sorghum-Sudan hybrids developed on the basis of CMS, and to determine heterosis according to the main economically valuable traits that affect green mass productivity. The study was carried out in theAgricultural Research Center “Donskoy” in 2020–2022. The objects of the study were the sorghum-Sudanese hybrids studied in the competitive variety testing. Sowing and field observations were carried out according to generally accepted methods. The meteorological conditions during the years of study (2020–2022) varied significantly, which made it possible to conduct a comprehensive estimation of hybrids in contrasting conditions. According to the study carried out according to the main traits (length of “sprouts-heading stage” period, plant height, length of the 3rd leaf and number of leaves per plant), which affect the productivity of sorghum-Sudan hybrids, there has been established a high heterotic effect. Hybrids developed on the basis of CMS had a green mass productivity of 3557–5949 g/m2 for two cuts. Hypothetical heterosis ranged from 59.8 to 144.3 %, true heterosis was 22.1–95.1 %. According to the green mass productivity, the hybrids ‘APV-1115 x Kudesnitsa’, ‘APV-1115 x Svetloplenchataya 2’, ‘APV-1115 x ChT-22’, ‘Dzhetta x ChT-22’ were the best ones, exceeding the standard on 755–1384 g/m2 or by 16.5–30.3 %. The identified hybrids have confirmed the expediency of using cytoplasmic male sterility to obtain a highly heterotic effect both in terms of green mass productivity and in terms of the main traits that affect productivity.